KEMAMPUAN GURU MENERAPKAN KETERAMPILAN PROSES SAINS DALAM PEMBELAJARAN IPA PADA SISWA SEKOLAH DASAR - Ika Candra Sayekti; Arum Mawar Kinasih (Profesi Pendidikan Dasar, 2017)
This research was intend to know the implementation of scientific process skills in elementary school of Muhammadiyah 14 Surakarta. It was qualitative research. The subject of this research was students on grade IV B. the data was obtained by observation, interview, and documentation. Observation was conducted by observing learning process on subject Science. The interview used to get data of scientific process skill that is planned on subject Science.  The documentation that was used was lesson plan an others. Data validation was conducted through triangulation. The results of this research were: teacher has prepared lesson plan that implement science process skill on its learning process, the teacher planned all the basic aspect of science process skills, such as: observing, classifying, measuring, predicting, inferring, and communicating. Along the learning process, the learning process was not conducted as written on learning process. The teacher got some hindrance to implement science process skill such as the minimum understanding of the teacher on science process skill and also teacher’s skill on time and class management.